What about Dinner? Chemical and Microresidue Analysis Reveals the Function of Late Neolithic Ceramic Pans - Jaromír Beneš; Valentina Todoroska; Kristýna Budilová; Jaromír Kovárník; Jaroslav Pavelka; Nevenka Atanasoska; Jiří Bumerl; Assunta Florenzano; Tereza Majerovičová; Václav Vondrovský; Michaela Ptáková; Petr Bednář; et al. (Molecules, 2021)
The Late Neolithic palafitte site, Ustie na Drim, in the northern part of Lake Ohrid (North Macedonia), excavated in 1962, offered ceramic fragments of large, flat, elongated pans. These artifacts could be dated by relative chronology to roughly around 5200–5000 BC. According to their shape and technological traits, the ceramic pans were probably used for baking. The attached materials on the surface of studied pan fragments were sampled for consequent chemical and microscopical analyses (i.e., analyses of starch, phytoliths, and microscopic animal remains). An immunological method revealed the presence of pork proteins in samples. The presence of organic residues of animal origin was, moreover, confirmed by the detection of cholesterol using gas chromatography coupled to mass spectrometry. Analysis of detected microscopic botanical objects revealed starch grains of several plants (i.e., oak, cattail, and grasses). An interesting find was the hair of a beetle larva, which could be interpreted contextually as the khapra beetle, a pest of grain and flour. Based on our data, we suppose that the ceramic pans from Ustie na Drim were used for the preparation of meals containing meat from common livestock in combination with cereals and wild plants.